2012
DOI: 10.1093/dnares/dss018
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput SNP Discovery and Genotyping for Constructing a Saturated Linkage Map of Chickpea (Cicer arietinum L.)

Abstract: The present study reports the large-scale discovery of genome-wide single-nucleotide polymorphisms (SNPs) in chickpea, identified mainly through the next generation sequencing of two genotypes, i.e. Cicer arietinum ICC4958 and its wild progenitor C. reticulatum PI489777, parents of an inter-specific reference mapping population of chickpea. Development and validation of a high-throughput SNP genotyping assay based on Illumina's GoldenGate Genotyping Technology and its application in building a high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
120
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 89 publications
19
120
1
1
Order By: Relevance
“…SNPs are now projected to become the most useful of genetic markers, especially for the construction of dense maps (Gaur et al, 2012). The distinguished feature of the genetic linkage map presented here is that, it has been assembled based on a single population utilizing segregation data of each of the SNP markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SNPs are now projected to become the most useful of genetic markers, especially for the construction of dense maps (Gaur et al, 2012). The distinguished feature of the genetic linkage map presented here is that, it has been assembled based on a single population utilizing segregation data of each of the SNP markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these maps are not comparable to the map reported here as they were composed from multiple marker types and several populations. In order to increase the number of markers in a particular genome of plants and animals, the consensus maps were computed, but the maps may have lacked in accuracy of the marker order (Gaur et al, 2012). Hence, the current map of this study may be considered more accurate regarding the marker order since the markers were distributed on the linkage groups based on recombination frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, transcriptome analysis by next generation sequencing (NGS), RNA-seq for sRNAs and their use in genOmics research, have greatly improved plant genomic resources. [20][21][22][23][24][25] Li et al, 26 identified 5365 differentially expressed probe sets (2-fold as cutoff) in the switch grass cultivar Alamo, under heat stress, utilizing switch grass Affy metrix gene chips. By comparative transcriptome analysis in response to heat stress, they identified 16 common genes in four monocots-switch grass, rice, wheat and maize.…”
Section: Transcriptomics: a Key To Understanding Abiotic Stress Respomentioning
confidence: 99%
“…The high frequency of SNPs compared to SSR markers makes SNPs the marker of choice (Gaur et al, 2012 Genetic variations leading to duplication, polyploidy and gene loss (canola, blackleg fungus (Golicz et al, 2015), wheat (Gornicki et al, 1997)) are very common in the evolution of plants. Legumes of the large Papilionoideae subfamily have undergone whole genome duplication (Cannon et al, 2006).…”
Section: Chickpea Variation Study Snp Density and Gene Loss 41 Intrmentioning
confidence: 99%